Динамическая модель структурно-функционального синтеза транспортной ТКС - Лемешко, О. В.; Стерин, В. Л. (Проблеми телекомунікацій, 2011)
The paper proposed a dynamic model of the structural-functional synthesis of transport telecommunication network (TCN). The model provides a consistent solution for problems of the choice of topology and channels bandwidth in TCN, flow distribution, and determine the order of connection fees to the nodes of the TCN.
Keywords: транспортная ТКС; динамическая модель